A study of the factors affecting the receding age of onset of menarche in young girls - Dharmarha, Noor; Konda, Anuradha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Present study highlights that the worldwide trend of declining age at menarche is also seen in urban Indian girls. The aim of the study was to evaluate the age of menarche and to find out the factors associated with the timing of menarche. Methods: The study was an observational cross sectional study. 258 healthy, menstruating, adolescent girls aged 10-16 years, were selected by simple random sampling. Pre-designed structured questionnaires were distributed after taking informed consent. Anthropometric measurements were taken using standard techniques. The average age of menarche was calculated. The association of the age at menarche with the proposed factors was analyzed using chi square test and Pearson’s correlation coefficient. “P value” less than 0.05 was considered as significant. Results: The mean age at menarche was found to be 12.23±1.09 years. The study found a strong association between the respondent’s age at menarche and her sister’s age at menarche (p=0.002). The study also found a strong association between age at menarche and the socioeconomic status (p=0.021). This study however found no association of menarcheal age with factors like birth weight, type of diet, frequency of milk intake, body mass index, waist hip ratio, amount of exercise, unstable environment at home and psychosocial stress. Conclusions: The worldwide trend of declining age at menarche is also seen in urban Indian girls. This trend underlines the importance of investigating the factors associated with it and studying the future implications of a lower age at menarche.